Collaborative Governance on Energy Management Online Reporting According To Energy Conservation Policy - Windaru, Akim; Kumorotomo, Wahyudi; Pitoyo, Agus Joko (STI Policy and Management Journal, 2024)
Energy savings in Indonesia are still far from the expected target of only around 79,358 GWh/141,220 GWh. The achievement is based on online reporting of energy management by industry according to government regulation No. 70 of 2009 which is reported regularly every year. This is done by the government as support in reducing the impact of climate change that occurs today. The qualitative method used in this study was a collaborative governance process approach between the government and industry with a collaborative governance cycle that occurs, is then analyzed, and conclusions drawn. The research results obtained include difficulties in identifying industries because there are still differences in authority within different government agencies. There are still 30% of industries that meet the requirements but have not done online energy management reporting including the fulfillment of all energy management activities that must be carried out. Articles related to incentives and disincentives that have not been fully implemented by the government. Collaborative governance is very important to be applied in the division of tasks, functions, and roles of each party involved. So that all can run according to their rights and responsibilities so that the achievement of future energy saving targets can be achieved.